Inheritable Effect of Unpredictable Maternal Separation on Behavioral Responses in Mice - Weiss, Isabelle C.; Franklin, Tamara B.; Vizi, Sándor; Mansuy, Isabelle M. (Frontiers in Behavioral Neuroscience, 2011)
The long-term impact of early stress on behavior and emotions is well documented in humans, and can be modeled in experimental animals. In mice, maternal separation during early postnatal development induces poor and disorganized maternal care, and results in behavioral deficits that persist through adulthood. Here, we examined the long-term effect of unpredictable maternal separation combined with maternal stress (MSUS) on behavior and its transmissibility. We report that unpredictable maternal separation from birth to postnatal day (PND) 14 in C57Bl/6J mice has mild behavioral effects in the animals when adult, but that its combination with maternal stress exacerbates this effect. Further, the behavioral deficits are transmitted to the following generation through females, an effect that is independent of maternal care and is not affected by cross-fostering. The combined manipulation does not alter basic components of the HPA axis but decreases the expression of the corticotropin releasing factor receptor 2 (CRFR2) in several nuclei of the amygdala and the hypothalamus in the brain of maternal-separated females. These results suggest a non-genomic mode of transmission of the impact of early stress in mice.